Prevalence of aldosterone breakthrough in dogs receiving renin‐angiotensin system inhibitors for proteinuric chronic kidney disease. (9th November 2022) - Ames, Marisa K.; Vaden, Shelly L.; Atkins, Clarke E.; Palerme, Jean‐Sebastien; Langston, Catherine E.; Grauer, Gregory F.; Shropshire, Sarah; Bove, Christina; Webb, Tracy
Abstract: Background: The influence of aldosterone breakthrough (ABT) on proteinuria reduction during renin‐angiotensin system (RAS) inhibition for spontaneous proteinuric chronic kidney disease (CKDP ) has not been determined in dogs. Objectives: Determine whether ABT occurs in dogs with CKDP and if it is associated with decreased efficacy in proteinuria reduction during RAS inhibitor treatment. Animals: Fifty‐six client‐owned dogs with CKDP and 31 healthy client‐owned dogs. Methods: Prospective, multicenter, open‐label clinical trial. Dogs were treated with an angiotensin‐converting enzyme inhibitor or angiotensin receptor blocker alone or in combination at the attending clinician's discretion and evaluated at 5 time points over 6 months. Healthy dogs were used to determine the urine aldosterone‐to‐creatinine ratio cutoff that defined ABT. The relationship of ABT (present at ≥50% of visits) and proteinuria outcome (≥50% reduction in urine protein‐to‐creatinine ratio from baseline at ≥50% of subsequent visits) was evaluated. Mixed effects logistic regression was used to evaluate the relationship between clinical variables and outcomes (either successful proteinuria reduction or ABT). Results: Thirty‐six percent (20/56) of dogs had successful proteinuria reduction. Between 34% and 59% of dogs had ABT, depending on the definition used. Aldosterone breakthrough was not associated with proteinuria outcome. Longer duration in the study was associated with greater likelihood of successful proteinuria reduction ( P  = .002; odds ratio, 1.6; 95% confidence interval [CI], 1.2‐2.2). Conclusions and Clinical Importance: Aldosterone breakthrough was common in dogs receiving RAS inhibitors for CKDp but was not associated with proteinuria outcome.